Bioinformatics-Assisted Discovery of Antioxidant Cyclic Peptides from Corn Gluten Meal - Hongcheng Liu; Tong Sun; He Gao; Xiaolong Liu; Shanshan Zhang; Tingting Liu; Dawei Wang; Hongxiu Fan; Yanrong Zhang (Foods)
Using a multidisciplinary approach, this paper was designed to prepare, identify, and characterize novel maize antioxidant cyclic peptides from protein hydrolysate of corn gluten meal (CGM). A bioinformatics approach was used to identify the best protease, and the results showed that papain+subtilisin was most likely to produce antioxidant cyclic peptides. The result of the enzymatic hydrolysis validation experiment showed that hydrolysate by papain+subtilisin yielded the highest concentration of cyclic peptide (67.14 ± 1.88%) and remarkable DPPH, ABTS, and hydroxyl radical scavenging rates (81.06 ± 2.23%, 82.82 ± 1.83%, and 47.44 ± 2.43%, respectively) compared to other hydrolysates. Eleven antioxidant cyclic peptides were identified in the protein hydrolysate of CGM through sequential purification and mass spectrometry analysis. The results of molecular docking analysis indicated that the cyclic peptides can form stable hydrogen bonds and hydrophobic interactions with the key amino acid residues of Kelch-like ECH-associated protein 1 (Keap1). Cyclic peptides may regulate the Keap1-Nrf2 pathway by occupying the Kelch domain of Keap1, inhibiting the ubiquitination degradation of Nrf2 (nuclear factor erythroid 2-related factor 2), thereby stabilizing the Nrf2 protein and activating the antioxidant gene network. This study underlined the bioinformatics approach for antioxidant cyclic peptide discovery, which is time- and cost-effective and promotes new cyclic peptide drugs or functional food development.